“The Renaissance Antiquity” in Works of Erwin Panofsky - Zakharova, Vera N. (Actual Problems of Theory and History of Art, 2015)
The article is dedicated to the conception of Italian Renaissance in the works of Erwin Panofsky. The main point of Panofsky’s conception is the idea of the Renaissance as the epoch of “the rebirth of antiquity”, which was formed to the full extent in his late book “Renaissance and renascences in Western Art” (1960).  In his works, Panofsky creates an idea of “normativity” of Italian Renaissance art. At the base of this concept lies the certainty in exceptional role of Renaissance art, which became a keynote of American researches in the 1920s–1950s. Formed by J. Burckhardt and H. Wölfflin, the image of the Italian Renaissance with its rising of personality was accordant with liberal values of American culture. One of the key components of the image of the “normative Renaissance” by Panofsky is the idea of “the Renaissance Antiquity”, which is discussed in the polemic context with works by A. Warburg in the paper.
Keywords: Erwin Panofsky; art of Italy; Renaissance; Antiquity